Proceedings 2017 Network and Distributed System Security Symposium 2017
DOI: 10.14722/ndss.2017.23408
|View full text |Cite
|
Sign up to set email alerts
|

Broken Hearted: How To Attack ECG Biometrics

Abstract: In this work we present a systematic presentation attack against ECG biometrics. We demonstrate the attack's effectiveness using the Nymi Band, a wrist band that uses electrocardiography (ECG) as a biometric to authenticate the wearer. We instantiate the attack using a hardware-based Arbitrary Waveform Generator (AWG), an AWG software using a computer sound card, and the playback of ECG signals encoded as .wav files using an off-the-shelf audio player. In two sets of experiments we collect data from a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 19 publications
1
41
0
Order By: Relevance
“…Reports show that large amounts of sensitive healthcare data are vulnerable to leakage or theft, or have already been compromised because of security lapses at hospitals, insurance companies or government agencies [26]. Adversaries may also easily obtain raw ECG signal from photos of ECG printouts, as has been shown in previous work [2].…”
Section: Ecgmentioning
confidence: 94%
See 3 more Smart Citations
“…Reports show that large amounts of sensitive healthcare data are vulnerable to leakage or theft, or have already been compromised because of security lapses at hospitals, insurance companies or government agencies [26]. Adversaries may also easily obtain raw ECG signal from photos of ECG printouts, as has been shown in previous work [2].…”
Section: Ecgmentioning
confidence: 94%
“…Earlier work authenticates users while they are being shown controlled stimuli, such as images [13] or moving shapes [14]. Eberz [19] Touch dynamics Assisted manual imitation Perfect [20] Touch dynamics Automatic (robot) None [21] Touch dynamics Automatic (robot) Perfect [22] Gait Assisted manual imitation Perfect [2] ECG Signal generator Cross-device users while they perform standard computer tasks (reading, typing, browsing and watching videos) [15]. Their featureset consists of temporal features reflecting short-term speed and acceleration, spatial features that measure the steadiness of the gaze and the changes of the pupil diameter.…”
Section: Biometric Authenticationmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather, they simply showed that they can disable all therapies, an attack which is easily detectable. Other examples are spoofing attacks on ICDs [16], attacks on insulin pumps and glucose monitors [18], and on electrocardiogram-based biometrics [6]. The work of Jiang et al [14] offers a model-based approach to analyze the accuracy ICD algorithms by conducting in-silico trials on synthetic cardiac signals.…”
Section: Related Workmentioning
confidence: 99%